2013
DOI: 10.1166/ch.2013.1007
|View full text |Cite
|
Sign up to set email alerts
|

Homeobox Gene Deregulation: Impact on the Hallmarks of Cancer

Abstract: Homeobox genes comprise a super-family of evolutionarily conserved genes that play essential roles in controlling body plan specification and cell fate determination. Substantial evidence indicates that leukemogenesis is driven by abnormal expression of homeobox genes that control hematopoiesis. In solid tumors, aberrant expression of homeobox genes has been increasingly found to modulate diverse processes such as cell proliferation, cell death, metastasis, angiogenesis and DNA repair. This review discusses ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 89 publications
(123 reference statements)
0
35
0
Order By: Relevance
“…A previous report demonstrated that 23 out of 39 HOX cluster genes are expressed in human adrenal glands and that HoxB2, B4, B5, and B9 are expressed in order from the capsule to the inner zona reticularis in the rat adrenal cortex (29). Because some HOX genes are involved in cellular differentiation and tumorigenesis (45), it is interesting to speculate that aberrant HOX gene activation contributes to tumorigenesis in APA.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report demonstrated that 23 out of 39 HOX cluster genes are expressed in human adrenal glands and that HoxB2, B4, B5, and B9 are expressed in order from the capsule to the inner zona reticularis in the rat adrenal cortex (29). Because some HOX genes are involved in cellular differentiation and tumorigenesis (45), it is interesting to speculate that aberrant HOX gene activation contributes to tumorigenesis in APA.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these diverse DNA-binding proteins have the potential to alter DNA damage signaling in tissue-specific ways correlating with their developmental programs. The effects of homeodomain proteins may also have important consequences in cancer since upregulation or misexpression of these transcription factors is observed in some tumor types ( Haria and Naora, 2013 ). Further work is clearly necessary to decipher the relationship between these factors and ATM activation in these different biological settings.…”
Section: Discussionmentioning
confidence: 99%
“…These included several homeobox genes (HOX), forkhead box (FOX) families, G protein-coupled receptors (GPR), and zinc finger proteins (ZNF) (Supplementary Table S3). HOX genes belong to a large family that encodes for proteins functioning as critical master regulatory transcription factors during embryogenesis; where some of them reported overexpressed while others downregulated in cancer8283. The roles of HOX genes methylation and downregulation in the biology of EAC or as biomarkers for cancer risk need to be determined.…”
Section: Resultsmentioning
confidence: 99%